Analisis Pengaruh Suasana Tempat, Kualitas Pelayanan, Kualitas Produk, Persepsi Harga, terhadap Loyalitas Kepuasan Pelanggan (Studi di pelanggan CoffeeShop Diantara Pontianak) - Dwiputra, Wahyu; A, Ahmadi; Listiana, Erna; Fitriana, Ana; G, Giriati (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study aims to analyze the influence of atmosphere, service quality, product quality, and price perception on customer loyalty through customer satisfaction as a mediating variable on Coffee Shop Diantara Pontianak customers. The population in this study were Coffee Shop Diantara consumers with a sample size of 182 respondents. The data analysis method used Partial Least Squares Structural Equation Modeling (PLS-SEM) with the help of Smart PLS 4.0 software. The results showed that atmosphere, service quality, and product quality had a significant positive effect on customer satisfaction, which in turn also had a significant positive effect on customer loyalty. In addition, customer satisfaction was proven to significantly mediate the influence of atmosphere, service quality, and product quality on customer loyalty. However, price perception did not have a significant effect on customer satisfaction or loyalty. This study is expected to contribute to Coffee Shop Diantara Pontianak managers in developing strategies to improve service quality to encourage sustainable customer loyalty.